Constructivist Negotiation Ethics - French, Warren (Journal of business ethics, 2002)
The success of Discourse Ethics is premised on the discovery and use of shared values. If this is true what type of negotiation style, especially when used in an intercultural setting, is best suited to make use of shared values. Research focusing on moral arguments between Germans and Americans uncovered an array of shared values. But the existence of shared values, by itself, was not an adequate predictor of a negotiation's success. What did prove to be a predictor of success was the use of a Constructivist style of negotiation by both parties.